The Changing Public Sector and the Contradiction of Economic Globalization - Sári, Nándor (Marketing & Menedzsment, 2019)
THE AIM OF THE PAPER This paper attempts to examine the impact that economic globalization has had on the public sector. In the past two decades, researchers have gradually turned their attention to international and global perspectives in their efforts to analyze the changing nature and patterns of welfare policies, development approaches and public sector systems. Accordingly, the aim of this study is to evaluate and discuss the characteristics of globalized economic processes in regard to policy-making and public service design. METHODOLOGY This study is based on mainstream literature review and secondary data analysis of the original data of OECD and World Bank report, with the aim of confirming the correlations between hyperglobalization – in other words, excessive economic liberalization associated with deep integration of markets and services – and public policy transformation. The study applies a research framework associated with public sector expenditure, economic openness and foreign trade patterns. MOST IMPORTANT RESULTS According to our results, the complex, contradictory impacts and processes of economic globalization contemporaneously have exacerbated socio-economic challenges, and have transformed the social dimensions of policy implementation. Furthermore, these multifaceted provocations have required active responses and solutions at international level. In addition, we identified that economic openness have positively correlated with public sector size — notwithstanding, the interpretation of the correlation may be influenced by several other factors, such as the “size” of nation-states. RECOMMENDATIONS The results suggest that improving public policy is indispensable for achieving good governance; and a proactive, adequate public sector might resolve the socio-economic issues that the market economy does not address. Therefore, a modernized public sector system, based on a multi-layered and multi-sectorial framework, could effectively reshape income distribution, combat poverty and counter threats related to globalization. Acknowledgements: The study has been funded by EFOP-3.6.3-VEKOP-16-2017-00007, “Young Researchers from Talented Students – Fostering Scientific Careers in Higher Education”.